Comparison of the Polyphenolic Profile of Medicago sativa L. and Trifolium pratense L. Sprouts in Different Germination Stages Using the UHPLC-Q Exactive Hybrid Quadrupole Orbitrap High-Resolution Mass Spectrometry - Elena Roxana Chiriac; Carmen Lidia Chiţescu; Daniela Borda; Mariana Lupoae; Cerasela Elena Gird; Elisabeta-Irina Geană; Giorgiana-Valentina Blaga; Rica Boscencu (Molecules, 2020)
Identification and quantification of polyphenols in plant material are of great interest since they make a significant contribution to its total bioactivity. In the present study, an UPLC-Orbitrap-MS/MS approach using the variable data acquisition mode (vDIA) was developed and applied for rapid separation, identification, and quantification of the main polyphenolic compounds in Medicago sativa L. and Trifolium pratense L. sprouts in different germination stages. Based on accurate MS data and fragment ions identification strategy, a total of 29 compounds were identified by comparing their accurate masses, fragment ions, retention times, and literatures. Additionally, a number of 30 compounds were quantified by comparing to the reference standards. Data were statistically analysed. For both plant species, the sprouts of the third germination day are valuable sources of bioactive compounds and could be used in phytotherapy and nutrition. Although Trifolium pratense L. (Red Clover) is considered to be a reference for natural remedies in relieving menopause disorders, alfalfa also showed a high level of biological active compounds with estrogenic activity.